2020
DOI: 10.3390/agronomy10121873
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Additives on Fermentation, Aerobic Stability and Volatile Organic Compounds in Whole-Crop Rye Silage

Abstract: Whole-crop cereal silage represents an important component of ruminant diets and is used as a substrate for biogas production. Due to the scarcity of data on whole-crop rye (Secale cereale L., WCR), our study aimed to evaluate the effects of a range of biological and chemical additives of different compositions on the fermentation and aerobic stability of silage made from this species. In addition, the production of various volatile organic compounds (VOCs), which potentially contribute to greenhouse gas emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
2
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 58 publications
4
8
2
1
Order By: Relevance
“…This clearly confirms the efficacy of LB inoculant in promoting a heterofermentative pathway. Compared with the findings of Auerbach et al [ 25 ] who ensiled whole-crop rye with various additives, lactic acid and, in particular acetic acid concentrations were considerably lower than those in the present experiment. This difference could be ascribed to the substantially lower DM concentration at ensiling in the current experiment (238 vs 439 g/kg), which is known to contribute to the increased fermentation rate and, thus accumulation of organic acids [ 12 ].…”
Section: Resultscontrasting
confidence: 89%
See 2 more Smart Citations
“…This clearly confirms the efficacy of LB inoculant in promoting a heterofermentative pathway. Compared with the findings of Auerbach et al [ 25 ] who ensiled whole-crop rye with various additives, lactic acid and, in particular acetic acid concentrations were considerably lower than those in the present experiment. This difference could be ascribed to the substantially lower DM concentration at ensiling in the current experiment (238 vs 439 g/kg), which is known to contribute to the increased fermentation rate and, thus accumulation of organic acids [ 12 ].…”
Section: Resultscontrasting
confidence: 89%
“…Untreated rye silages remained nearly 8 h more stable than LP silages, signifying that aerobic stability was exacerbated with LP inoculation. Auerbach et al [ 25 ] reported that whole-crop rye silage with no additive was stable for approximately 19 h after aerobic exposure, which is less than the value obtained in this experiment. This discrepancy could possibly be because of the difference in DM concentration of rye forage between two studies which was much lower in our experiment (236 vs 419 g/kg).…”
Section: Resultscontrasting
confidence: 82%
See 1 more Smart Citation
“…Acetic acid concentration in the LB-treated silages maintained at the typical range of 3-4% as the previous report [54]. The substantially high acetic acid formation in LB-treated silage could be explained with the promotion of heterofermentative metabolism in this treatment [20,24,56].…”
Section: Organic Acid Changes During Ensilingsupporting
confidence: 81%
“…Although the presence of epiphytic LAB on forage biomass surfaces can naturally initiate ensiling fermentation, microbial inoculants are usually recommended to support rapid acidification, which improves fermentative quality, and minimizes nutrient degradation during fermentation [20,21]. Previous studies identified that microbial inoculants such as Lactobacillus plantarum (LP) and L. buchneri (LB), individually or in combination, enhanced the fermentative quality of cereal grain and grass silages [22][23][24]. However, inoculation with both homofermentative and heterofermentative LAB has provided inconsistent results when tested at variable moisture levels [25].…”
Section: A C C E T E Dmentioning
confidence: 99%